ChemInform Abstract: Br2‐Catalyzed Regioselective Dehydrative Coupling of Indoles with Acyloins: Direct Synthesis of α‐(3‐Indolyl) Ketones. Issue 31 (14th July 2016) - Liang, Deqiang; Li, Xiangguang; Li, Yanni; Yang, Yungang; Gao, Shulin; Cheng, Ping
Abstract: In this reaction Br2 serves as a Lewis acid.